The analysis of the contribution of telecommunications sector to the economic development of Uganda for the period 1994-1999 : case stud y; Uganda Telecom Limited - Mugisha, Mario Sidney (Kampala : Makerere University, 2000)
Dissertation (B.Sc., Quant.Econ.) - Makerere University, 2000
Includes bibliographical references (p.39)
Keywords: Telecommunications -- Uganda